Sozialräumliche Monitoringsysteme. Ein Vergleich quantitativer Herangehensweisen für städtische Sozialraummonitorings im deutschsprachigen Raum - Speringer, Markus; Böing, Mira (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Cities are centres of social, cultural, economic and material diversity, where people in the most diverse living situations meet in densely populated areas and where social inequalities or disparities can manifest and intensify through the spatial concentration of population groups. Due to the increase in inner-city disparities, numerous German-speaking (large) cities have started to establish small-scale social area reports in order to be able to counteract the spatial concentration of social problems at an early stage. This paper systematically analyses and discusses the different methodological-conceptual approaches to quantitative social area analyses in 25 Germanspeaking (large) cities with comparable data material. The systematic comparison of motivations, goals and content-related questions as well as the indicators, spatial levels of analysis and methodological approaches used are of interest for this meta-analysis. The knowledge gained can be of relevance for urban and regional administrations when (re)designing and implementing their own social area analyses.